Thesis-Antithesis-Neutrothesis, and Neutrosynthesis - Florentin Smarandache (Neutrosophic Sets and Systems, 2015)
In this short paper we extend the dialectical triad thesis-antithesis-synthesis (dynamics of and <antiA>, to get a synthesis) to the neutrosophic tetrad thesis-antithesis-neutrothesis-neutrosynthesis (dynamics of , <antiA>, and <neutA>, in order to get a neutrosynthesis). We do this for better reflecting our world, since the neutralities between opposites play an important role. The neutrosophic synthesis (neutrosynthesis) is more refined that the dialectical synthesis. It carries on the unification and synthesis regarding the opposites and their neutrals too.